Polyamine metabolic canalization in response to drought stress in Arabidopsis and the resurrection plant Craterostigma plantagineum - Alcázar, Rubén (Landes Bioscience, 2011)
In this work, we have studied the transcriptional profiles of polyamine biosynthetic genes and analyzed polyamine metabolic fluxes during a gradual drought acclimation response in Arabidopsis thaliana and the resurrection plant Craterostigma plantagineum. The analysis of free putrescine, spermidine and spermine titers in Arabidopsis arginine decarboxylase (adc1–3, adc2–3), spermidine synthase (spds1–2, spds2–3) and spermine synthase (spms-2) mutants during drought stress, combined with the quantitative expression of the entire polyamine biosynthetic pathway in the wild-type, has revealed a strong metabolic canalization of putrescine to spermine induced by drought. Such canalization requires spermidine synthase 1 (SPDS1) and spermine synthase (SPMS) activities and, intriguingly, does not lead to spermine accumulation but to a progressive reduction in spermidine and spermine pools in the wild-type. Our results suggest the participation of the polyamine back-conversion pathway during the drought stress response rather than the terminal catabolism of spermine. The putrescine to spermine canalization coupled to the spermine to putrescine back-conversion confers an effective polyamine recycling-loop during drought acclimation. Putrescine to spermine canalization has also been revealed in the desiccation tolerant plant C. plantagineum, which conversely to Arabidopsis, accumulates high spermine levels which associate with drought tolerance. Our results provide a new insight to the polyamine homeostasis mechanisms during drought stress acclimation in Arabidopsis and resurrection plants.